Can Monetary Policy Affect Economic Activity under Surplus Liquidity? Some Evidence from Macedonia. - Branimir Jovanovic; Aneta Krstevska; Neda Popovska-Kamnar (National Bank of the Republic of Macedonia, 2015)
Surplus liquidity in the banking system changes the monetary transmission mechanism, reducing the effectiveness of the traditional instrument, the interest rate. In this paper we examine the real effects of several monetary-policy instruments in Macedonia, an economy characterized by surplus liquidity. We use regime-switching Vector Autoregressions and track the responses of different economic activity indicators to changes in the monetary policy instruments. Our findings suggest that the interest rate channel is weakly effective in Macedonia. The responses to the other instruments are not very sizeable, either, but are significant. This implies that monetary policy can affect economic activity through the reserve requirement and the offered amount of central bank bills. These findings have implications for both the analysis and the conduct of monetary policy in economies with surplus liquidity. Regarding analysis, the implication is that the traditional approach, which considers only the role of the interest rate, is likely to lead to wrong conclusions. Regarding conduct, the implication is that monetary authorities, besides on the price impact of the interest rate, should additionally rely on the reserve requirement and other available instruments producing volume impact.
Keywords: E50; E52; 330; monetary policy; surplus liquidity; excess liquidity; VAR; Macedonia